Graphics for learning proven guidelines for planning, designing, and evaluating visuals in training materials - Clark, Ruth Colvin (Pfeiffer essential resources for training and HR professionals., 2011)
This second edition of the bestselling book summarizes guidelines for best use of graphics for instructional materials, including multimedia, texts, classroom aids, and slides used for briefings. These guidelines are based on updated scientific research and contain illustrative examples including examples for readers without a background in psychology. The authors help trainers tie graphics into their lesson topics and include facts, concepts, processes, procedures, and principles. The book discusses technical and environmental issues (such as bandwidth or screen size) that will influence how instructional professionals can apply the guidelines"